The Influence Of Accounting Knowledge, Socialization Of Accounting Standards, Education And Business Scale On The Quality Of Financial Statements (Study on SME in Bengkulu City) - Annisa Qurrata A’yun; Isma Coryanata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The development of SME in Bengkulu City is increasing from year to year, but in running their business, SMEs rarely make financial statements in accordance with SAK EMKM, this is due to the low accounting knowledge and education possessed by SME. In addition, it is very rare for socialization about SAK EMKM by the government. Business size will also affect SME in improving the quality of financial statements. This study aims to determine the influence of accounting knowledge, socialization of accounting standards, education and business scale on the quality of financial statements in SME in Bengkulu City. Data collection was done by questionnaire and data analysis using multiple linear regression analysis and hypothesis test. The sample in this study was 88 SME in the city of Bengkulu. The results showed that accounting knowledge, socialization of accounting standards and business scale had a significant partial effect on the quality of financial statements because the quality of financial statements could be improved due to accounting knowledge from SME and socialization from the government about SAK EKM and business scale. However, the variable level of education does not have a significant effect on the quality of financial statements because high education does not guarantee that someone can produce quality financial statements, without high education, SME can find out about the quality of good financial statements through socialization and training